Multi-layer vacuum coating method for enhancing surface of high-precision metal part
Through multi-layer vacuum coating technology, the problems of thermal deformation, wear resistance and high friction environment are solved in the surface treatment of high-precision metal parts, and the coating effect of high hardness and low friction self-lubricating is achieved.
Patent Information
- Application Number
- CN202411611918.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems in the surface treatment of high-precision metal parts such as thermal deformation, wear resistance, insufficient fatigue resistance, and need to rely on external lubrication in high friction environments.
The substrate is treated by plasma cleaning and laser etching, and a metal transition layer and a multi-layer nanohard coating are deposited, and a self-lubricating coating is deposited on it, and finally ion beam assisted deposition and low-temperature heat treatment are carried out.
It realizes the deposit of high-hardness and multi-layer coatings under low temperature conditions, reduces thermal deformation, improves the hardness, fatigue resistance and wear resistance of the coating, and achieves the low friction self-lubricating effect while maintaining the hardness of the coating.
Smart Images

Figure CN119592950A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, in particular to a multi-layer vacuum coating method for enhancing the surface of high-precision metal parts. Background Art
[0002] In modern manufacturing, the surface performance requirements of high-precision metal parts are getting higher and higher, especially in the fields of aerospace, automobile manufacturing, precision molds and medical equipment. The surface of metal parts not only needs to have high hardness and wear resistance, but also needs to have excellent corrosion resistance, low friction and good bonding force. Traditional surface treatment technologies, such as chrome plating, electroplating, single-layer chemical vapor deposition, etc., can meet the requirements in some aspects, but often have limitations.
[0003] First, although high-temperature chemical vapor deposition technology can deposit high-hardness coatings, its high-temperature process conditions will cause significant thermal deformation effects on the substrate, especially heat-sensitive metal materials, resulting in a decrease in the dimensional accuracy of parts, limiting the application of this technology in high-precision parts. Secondly, single-layer coatings are limited in wear resistance and fatigue resistance, and are prone to crack propagation and peeling problems, which cannot meet the requirements under long-term high-load conditions.
[0004] In addition, friction and lubrication issues are particularly important in precision machinery and high-speed equipment. Traditional coatings often require additional lubricants in high-friction environments, increasing the operating cost and maintenance frequency of the equipment. Although self-lubricating coating technologies such as molybdenum disulfide coatings have been applied, how to effectively combine hard coatings and self-lubricating layers in a multi-layer coating system is still a technical difficulty. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a multi-layer vacuum coating method for surface enhancement of high-precision metal parts, which solves the problem that the existing high-temperature coating deposition process easily causes thermal deformation of heat-sensitive metal parts, and at the same time, the single-layer coating has deficiencies in wear resistance, fatigue resistance and bonding strength, and it needs to rely on external lubrication in a high-friction environment, and cannot achieve a low-friction self-lubricating effect while maintaining the hardness of the coating.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A multi-layer vacuum coating method for surface enhancement of high-precision metal parts, comprising the following steps:
[0007] S1. Surface treatment: plasma cleaning is used to remove pollutants and oxide layers on the substrate surface, and laser etching technology is used to roughen the substrate surface at a microscopic level;
[0008] S2, coating deposition: depositing a metal transition layer on the substrate by plasma enhanced physical vapor deposition technology, and depositing a multi-layer nano hard coating on the transition layer;
[0009] S3, self-lubricating layer deposition: self-lubricating coating is deposited on the multi-layer nano-hard coating by pulsed laser deposition technology;
[0010] S4, post-treatment: the coating is post-treated using ion beam assisted deposition technology;
[0011] S5. Heat treatment: Perform low-temperature heat treatment on the coating to eliminate the internal stress of the coating.
[0012] Preferably, in the step S1, the plasma cleaning gas is argon, the gas flow rate is 200 sccm to 400 sccm, the plasma power is 300 W to 600 W, the cleaning time is 10 min to 30 min, and the processing pressure is controlled at 0.05 Pa to 0.2 Pa.
[0013] Preferably, in step S1, the laser etching technology uses a nanosecond laser with a wavelength of 1064 nm and a laser energy density of 8 J / cm 2 ~12J / cm 2 , the laser frequency is 10Hz~20Hz, the scanning speed is 2mm / s~5mm / s, and the surface roughness is controlled at 0.2μm~0.5μm.
[0014] Preferably, in the step S2, the metal transition layer includes a titanium layer and a chromium layer, the thickness of the titanium layer is 100nm to 300nm, the thickness of the chromium layer is 100nm to 200nm, the metal transition layer is deposited by plasma enhanced physical vapor deposition technology, and the substrate temperature is controlled at 200°C to 300°C.
[0015] Preferably, in step S2, the multilayer nano-hard coating comprises alternately deposited titanium nitride and chromium nitride, the thickness of a single coating layer is 40 nm to 120 nm, the total coating thickness is 3 μm to 10 μm, and the number of layers is 50 to 150 layers.
[0016] Preferably, in step S2, the coating hardness is calculated by the following formula:
[0017] σ y =σ 0 +k y ·d -0.5
[0018] Among them, σ y is the yield strength of the coating, σ 0 is the yield strength of defect-free grain material, k yis the material constant, d is the grain size, and the grain size is controlled between 30nm and 70nm to further improve the hardness and fatigue resistance of the coating.
[0019] Preferably, in the step S3, the self-lubricating coating comprises diamond-like carbon and molybdenum disulfide, the thickness of the self-lubricating coating is 300nm to 700nm, and the self-lubricating coating is deposited at a substrate temperature of 200°C to 300°C using pulsed laser deposition technology.
[0020] Preferably, in step S4, the ion beam energy of the ion beam assisted deposition technology is 800eV to 1500eV, and the ion beam current density is 8mA / cm 2 ~15mA / cm 2 The processing time is 20min to 40min.
[0021] Preferably, in the step S5, the low-temperature heat treatment step of the coating is carried out under the protection of an inert gas, the heat treatment temperature is 150° C. to 250° C., and the treatment time is 1 h to 3 h.
[0022] Preferably, in step S5, the friction coefficient of the coating is calculated by the following formula:
[0023]
[0024] Where μ is the friction coefficient, F friction is the friction force, F normal is the normal force, and the friction coefficient between diamond-like carbon and MoS self-lubricating coating is controlled in the range of 0.05 to 0.1.
[0025] The present invention provides a multi-layer vacuum coating method for surface enhancement of high-precision metal parts. It has the following beneficial effects:
[0026] 1. The present invention deposits multi-layer nano-coatings at low temperatures below 300°C through plasma enhanced PVD and pulsed laser deposition technology, reducing the thermal deformation problem caused by traditional high-temperature processes on heat-sensitive metal substrates. The low-temperature deposition process ensures that the coating can still form a multi-layer coating with high hardness and high density without affecting the dimensional accuracy of the substrate, making it more widely used in the surface treatment of high-precision parts.
[0027] 2. The present invention forms a multilayer composite structure by alternately depositing titanium nitride and chromium nitride nano-coatings, thereby improving the hardness, fatigue resistance and wear resistance of the coating. The nano-scale grain design of the multi-layer structure effectively reduces stress concentration and crack propagation, increases the durability and crack resistance of the coating, and at the same time improves the overall fatigue resistance of the coating through the Hall-Petch effect, making it suitable for harsh mechanical working conditions.
[0028] 3. The present invention introduces diamond-like carbon and molybdenum disulfide self-lubricating coatings into the outer layer of the multi-layer hard coating, thereby integrating the self-lubricating function into the hard coating system, so that the coating exhibits an extremely low friction coefficient and excellent wear resistance in a high-friction, dry-friction environment, thereby extending the service life of the parts, thereby effectively reducing friction, reducing equipment maintenance costs and operating energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a flow chart of the method steps of the present invention;
[0030] Figure 2 is a process flow chart of the present invention;
[0031] Figure 3 This is a distribution diagram of the coating structure of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1:
[0034] Please refer to the attached Figure 1 -Attached Figure 3 The embodiment of the present invention provides a multi-layer vacuum coating method for surface enhancement of high-precision metal parts, comprising the following steps:
[0035] S1. Surface treatment: plasma cleaning is used to remove pollutants and oxide layers on the substrate surface, and laser etching technology is used to roughen the substrate surface at a microscopic level;
[0036] S2, coating deposition: depositing a metal transition layer on the substrate by plasma enhanced physical vapor deposition technology, and depositing a multi-layer nano hard coating on the transition layer;
[0037] S3, self-lubricating layer deposition: self-lubricating coating is deposited on the multi-layer nano-hard coating by pulsed laser deposition technology;
[0038] S4, post-treatment: the coating is post-treated using ion beam assisted deposition technology;
[0039] S5. Heat treatment: Perform low-temperature heat treatment on the coating to eliminate the internal stress of the coating;
[0040] In step S1, the plasma cleaning gas is argon, the gas flow rate is 200 sccm to 400 sccm, the plasma power is 300 W to 600 W, the cleaning time is 10 min to 30 min, and the processing pressure is controlled at 0.05 Pa to 0.2 Pa;
[0041] In step S1, the laser etching technology uses a nanosecond laser with a wavelength of 1064nm and a laser energy density of 8J / cm 2 ~12J / cm 2 , the laser frequency is 10Hz~20Hz, the scanning speed is 2mm / s~5mm / s, and the surface roughness is controlled at 0.2μm~0.5μm;
[0042] In step S2, the metal transition layer includes a titanium layer and a chromium layer, the thickness of the titanium layer is 100nm to 300nm, the thickness of the chromium layer is 100nm to 200nm, the metal transition layer is deposited by plasma enhanced physical vapor deposition technology, and the substrate temperature is controlled at 200°C to 300°C;
[0043] In step S2, the multilayer nano hard coating includes alternate deposition of titanium nitride and chromium nitride, the thickness of a single layer coating is 40nm to 120nm, the total coating thickness is 3μm to 10μm, and the number of layers is 50 to 150 layers;
[0044] In step S2, the coating hardness is calculated using the following formula:
[0045] σ y =σ 0 +k y ·d -0.5
[0046] Among them, σ y is the yield strength of the coating, σ 0 is the yield strength of defect-free grain material, k y is the material constant, d is the grain size, and the grain size is controlled at 30nm to 70nm to further improve the hardness and fatigue resistance of the coating;
[0047] In step S3, the self-lubricating coating includes diamond-like carbon and molybdenum disulfide, the thickness of the self-lubricating coating is 300nm to 700nm, and the self-lubricating coating is deposited at a substrate temperature of 200°C to 300°C using a pulsed laser deposition technique;
[0048] In step S4, the ion beam energy of the ion beam assisted deposition technology is 800eV to 1500eV, and the ion beam current density is 8mA / cm 2 ~15mA / cm 2 , the processing time is 20min~40min;
[0049] In step S5, the low-temperature heat treatment step of the coating is carried out under the protection of an inert gas, the heat treatment temperature is 150° C. to 250° C., and the treatment time is 1 h to 3 h;
[0050] In step S5, the friction coefficient of the coating is calculated by the following formula:
[0051]
[0052] Where μ is the friction coefficient, F friction is the friction force, F normal is the normal force, and the friction coefficient between diamond-like carbon and MoS self-lubricating coating is controlled in the range of 0.05 to 0.1.
[0053] Summary of the Example: This example fully demonstrates the advantages of multi-layer coating structure design and low temperature deposition process, especially the protection of heat-sensitive substrates. Through the combination of PVD alternate deposition of multi-layer alternating structure and self-lubricating layer, the coating not only has excellent hardness and wear resistance, but also can effectively reduce the friction coefficient and extend the coating life.
[0054] Example 2: High temperature coating deposition process optimization solution
[0055] Implementation steps:
[0056] Substrate pretreatment: The stainless steel substrate was mechanically polished and plasma cleaned, with an argon flow rate of 400 sccm, a power of 600 W, and a cleaning time of 15 minutes.
[0057] Transition layer deposition: Plasma enhanced PVD technology was used to deposit a chromium (Cr) transition layer with a thickness of 150 nm and a deposition temperature of 300°C.
[0058] Multilayer hard coating deposition: Use chemical vapor deposition (CVD) technology to deposit chromium nitride multilayer coating, each layer thickness 80nm, total thickness 8μm, deposition temperature 500℃, to improve the coating's wear resistance and high temperature corrosion resistance.
[0059] Self-lubricating coating deposition: MoS2 coating was deposited by PLD technique with a coating thickness of 600nm and a substrate temperature of 300°C.
[0060] Ion beam assisted deposition: Ion beam assisted treatment was introduced during the deposition process, with an ion beam energy of 1200 eV and a treatment time of 40 minutes.
[0061] Post-treatment: A heat treatment process is adopted, the heat treatment temperature is 400°C, the time is 2 hours, and the atmosphere is an inert gas argon.
[0062] Summary of embodiments:
[0063] This embodiment uses a relatively high temperature coating deposition process, which is suitable for high temperature resistant materials such as stainless steel substrates. By combining the CVD deposition process with high temperature heat treatment, the high temperature resistance and corrosion resistance of the coating are enhanced. This process can significantly increase the service life of the coating in high temperature and harsh environments, but it is not applicable to heat-sensitive materials.
[0064] Example 3: Thickness-optimized gradient coating solution
[0065] Implementation steps:
[0066] Substrate pretreatment: Plasma cleaning of titanium alloy substrate, argon flow rate 200sccm, power 300W, cleaning time 10 minutes; laser etching using 10J / cm 2 The energy density is used for micro-etching.
[0067] Transition layer deposition: The Ti / Cr transition layer was deposited using PE-PVD technology, with a Ti layer thickness of 100 nm and a Cr layer thickness of 100 nm. The substrate temperature was 250 °C.
[0068] Gradient coating deposition: A gradient transition layer from Ti to titanium nitride is formed by regulating the gas flow rate, with a deposition thickness of 1 μm, followed by deposition of a chromium nitride coating with a thickness of 4 μm, and a total coating thickness of 5 μm.
[0069] Self-lubricating coating deposition: PLD was used to deposit diamond-like carbon coating with a coating thickness of 400 nm and a substrate temperature of 200 °C.
[0070] Ion beam assisted deposition: using ion beam assisted technology, ion beam energy 900eV, processing time 25 minutes.
[0071] Low temperature heat treatment: The low temperature heat treatment temperature is 180℃, the time is 1 hour, and the protection is nitrogen.
[0072] Summary of embodiments:
[0073] This embodiment optimizes the thickness distribution of the coating and uses a gradient transition coating to effectively reduce the stress concentration at the interface between the coating and the substrate, thereby avoiding peeling and cracking of the coating under high stress or alternating hot and cold conditions. At the same time, the self-lubricating coating is achieved under low temperature conditions and is suitable for a variety of application scenarios.
[0074] Example 4: Design of superhard coating on the surface of micro-mechanical parts
[0075] Implementation steps:
[0076] Substrate pretreatment: The surface of the micro titanium alloy parts was cleaned by ultrasonic cleaning combined with argon plasma cleaning, with a gas flow rate of 200 sccm, a power of 400 W, and a cleaning time of 5 minutes.
[0077] Transition layer deposition: The Ti layer was deposited using PE-PVD technology with a thickness of 150 nm and the substrate temperature was controlled at 150 °C.
[0078] Ultra-hard coating deposition: Pulsed laser is used to deposit ultra-hard titanium carbide (TiC) coating, with a single layer thickness of 50nm and a total thickness of 3μm. The hardness of the coating is greatly improved, and the deposition temperature is 200℃.
[0079] Self-lubricating coating deposition: Diamond-like carbon coating was deposited by PLD technique with a thickness of 500 nm and a substrate temperature of 200 °C.
[0080] Ion beam assisted deposition: ion beam energy 1000eV, processing time 20 minutes, increase the density of the coating.
[0081] Post-treatment: low temperature heat treatment, temperature is 150 ° C, time is 1.5 hours, atmosphere protection is nitrogen.
[0082] Summary of embodiments:
[0083] This embodiment is designed for micro-mechanical parts and uses a combination of super-hard coating and diamond-like carbon, which greatly improves the hardness and wear resistance of the coating while maintaining the self-lubricating properties and reducing the wear and friction of micro-mechanical parts. This design is very suitable for the application of micro-precision mechanical parts.
[0084] Example 5: Scheme for enhancing corrosion resistance and wear resistance of composite coating
[0085] Implementation steps:
[0086] Substrate pretreatment: The stainless steel 316L substrate was plasma cleaned with a gas flow rate of 350 sccm, a power of 500 W, and a cleaning time of 25 minutes.
[0087] Composite transition layer deposition: The composite transition layer of Ti and Cr was deposited by PE-PVD technology, with Ti / Cr thickness of 200 nm respectively, and the substrate temperature was set to 300 °C.
[0088] Composite coating deposition: CrC (chromium carbide) coating is added to the multilayer titanium nitride / chromium nitride coating to form a composite coating with a single layer thickness of 50-120nm and a total coating thickness of 6μm.
[0089] Self-lubricating coating deposition: MoS2 coating was deposited by PLD with a coating thickness of 400 nm and a substrate temperature of 300 °C.
[0090] Ion beam assisted deposition: ion beam energy 1200 eV, processing time 35 minutes.
[0091] High temperature heat treatment: The high temperature heat treatment temperature is 350℃, the time is 2 hours, and the nitrogen protection is used.
[0092] Summary of embodiments:
[0093] This embodiment significantly improves the wear resistance and corrosion resistance of the coating by introducing a CrC (chromium carbide) composite coating into the multi-layer coating structure. Combined with the molybdenum disulfide self-lubricating layer, the coating not only has strong corrosion resistance, but also exhibits low friction characteristics, and is suitable for parts in marine equipment and chemical industries that are exposed to corrosive environments for a long time.
[0094] Summary:
[0095] Embodiment 1 (the solution of the present invention) realizes high hardness, wear resistance and self-lubricating performance of the coating on the heat-sensitive substrate through low-temperature deposition and multi-layer structure design, reflecting the wide process applicability and performance advantages.
[0096] The second embodiment optimizes the high-temperature coating deposition process, which is particularly suitable for parts used under high-temperature conditions such as stainless steel, and enhances the high-temperature tolerance and corrosion resistance of the coating.
[0097] Embodiment 3 reduces interface stress through gradient coating design, is suitable for a variety of substrates and working conditions, and optimizes the fatigue resistance and bonding strength of the coating.
[0098] Embodiment 4 is specially designed for micro-mechanical parts. It uses a super-hard coating to improve the hardness and wear resistance of the coating while maintaining low friction performance, and is suitable for surface treatment of precision parts.
[0099] Embodiment 5 has enhanced corrosion resistance and wear resistance through the composite coating structure, is particularly suitable for application in harsh corrosive environments, and has excellent long-term stability.
[0100] Through the design of these five embodiments, it can be seen that the multi-layer vacuum coating method of the present invention has wide applicability, and can cope with different working conditions and substrate characteristics by adjusting process parameters and material combinations, which fully reflects the beneficial effects of the present invention.
[0101] Test experiment
[0102] process:
[0103] 1. Coating thickness and surface morphology test:
[0104] Test method: Use an ellipsometer to measure the total thickness of the coating with an accuracy of 1nm. Use a scanning electron microscope to observe the cross-sectional morphology of the coating and evaluate the density and interlayer structure of the coating.
[0105] Test purpose: To ensure that the coating thickness meets the design requirements and to observe the uniformity and integrity of the multi-layer structure.
[0106] 2. Hardness test:
[0107] Test method: Use nanoindenter to test hardness, and calculate coating hardness according to Oliver-Pharr method. Perform 10 indentation tests on each sample and take the average value.
[0108] Purpose of the test: To evaluate the hardness level of the coating, especially the effect of the nano multilayer structure on the hardness improvement.
[0109] 3. Wear resistance test:
[0110] Test method: The wear resistance test was conducted using a ball-on-disc wear tester, with a steel ball (hardness 60HRC, diameter 6mm) used as the counter-wear material. The test load was 10N, the sliding speed was 0.1m / s, and the test distance was 1000m. The wear rate was calculated by measuring the wear scar depth and width.
[0111] Test purpose: To evaluate the wear resistance of coatings, especially the friction and wear reduction effect of self-lubricating coatings.
[0112] 4. Friction coefficient test:
[0113] Test method: Also use the ball-on-disc wear tester to record the friction force and calculate the friction coefficient.
[0114] Purpose of the test: To evaluate the coefficient of friction of self-lubricating coatings and determine how different coatings perform in a friction environment.
[0115] 5. Coating adhesion test:
[0116] Test method: A scratch tester was used to evaluate the coating adhesion. The loading force was gradually increased from 0N to 80N, and the critical load for coating peeling was recorded.
[0117] Purpose of the test: To evaluate the bonding strength between the coating and the substrate, especially the enhancing effect of the transition layer and ion beam treatment on the bonding strength.
[0118] 6. Corrosion resistance test:
[0119] Test method: Use electrochemical impedance spectroscopy to test the corrosion resistance of the coating in 3.5% NaCl solution. Test the corrosion potential and corrosion current density, and calculate the corrosion rate of the coating.
[0120] Test purpose: To evaluate the corrosion resistance of the coating and determine the stability of each embodiment in a corrosive environment.
[0121] Experimental data between embodiments:
[0122] The following is a summary of specific test data and results for the above five embodiments.
[0123]
[0124] Test results analysis and summary:
[0125] Embodiment 1:
[0126] Hardness: The coating hardness of the present invention is 22.5 GPa, showing a relatively high hardness level. The multilayer titanium nitride / chromium nitride nano-coating structure forms a dense coating structure at low temperatures, and the self-lubricating layer ensures good friction performance.
[0127] Wear rate: The wear rate of the embodiment of the present invention is 1.25×10 -6 mm 3 / N·m, showing excellent wear resistance. The introduction of self-lubricating coating reduces friction on the coating surface and reduces wear.
[0128] Friction coefficient: The friction coefficient is 0.08, which is significantly lower than that of other embodiments, proving the good lubrication effect of the composite coating of diamond-like carbon and molybdenum disulfide.
[0129] Bonding strength: The bonding strength reaches 62.5N, indicating that the bonding strength between the coating and the substrate is significantly enhanced through the plasma enhanced PVD process and ion beam assisted treatment.
[0130] Corrosion resistance: The corrosion potential is -0.25V and the corrosion rate is 0.016mm / year, showing good corrosion resistance and suitable for applications in a variety of complex environments.
[0131] Example 2 (optimization of high temperature coating deposition process):
[0132] Hardness: Due to the high temperature deposition process, the coating hardness is slightly lower than that of Example 1 (20.8 GPa), but still exhibits good wear resistance.
[0133] Wear rate: Wear rate is 1.40×10 -6 mm 3 / N·m, which is slightly higher than that of the solution of the present invention, indicating that the density of the coating formed under high temperature conditions is slightly poor.
[0134] Friction coefficient: The friction coefficient is 0.12, and the self-lubricating effect is not as good as that of the solution of the present invention.
[0135] Binding strength: The binding strength is 58N. Although high temperature treatment is adopted, the binding strength is slightly lower than that of the solution of the present invention, which indicates that the contribution of high temperature treatment to the binding strength is limited.
[0136] Corrosion resistance: The corrosion potential is -0.30V, and the corrosion rate is 0.020mm / year, which is slightly worse than the solution of the present invention and is suitable for high-temperature corrosion environments.
[0137] Example 3 (Gradient Coating Optimization):
[0138] Hardness: The gradient coating design enables the coating hardness to reach 21.7 GPa, which is close to the level of the solution of the present invention.
[0139] Wear rate: Wear rate is 1.30×10 -6 mm 3 / N·m, indicating that the gradient coating has better wear resistance than Example 2, but not as good as Example 4.
[0140] Friction coefficient: The friction coefficient is 0.10, and the self-lubricating effect is good, but still lower than the solution of the present invention.
[0141] Bonding force: The bonding force is 60.3N. The gradient coating has obvious advantages in stress distribution, and the bonding force is better than that of Example 2.
[0142] Corrosion resistance: The corrosion potential is -0.28V and the corrosion rate is 0.018mm / year, showing good corrosion resistance.
[0143] Embodiment 4 (superhard coating of micro-mechanical parts):
[0144] Hardness: The coating in this embodiment has the highest hardness, which is 24 GPa, proving that the superhard TiC coating has a significant effect on improving the hardness.
[0145] Wear rate: Wear rate is 1.10×10 -6 mm 3 / N·m, showing excellent wear resistance, suitable for micro-mechanical parts.
[0146] Friction coefficient: The friction coefficient is 0.06, the lowest friction coefficient shows that this design performs well in reducing friction loss and is suitable for high-precision mechanical applications.
[0147] Bonding force: The bonding force is 61.5N. The higher bonding force ensures the durability of the coating.
[0148] Corrosion resistance: The corrosion potential is -0.26V and the corrosion rate is 0.015mm / year, showing good corrosion resistance.
[0149] Embodiment 5 (composite coating corrosion resistance scheme):
[0150] Hardness: The hardness is 21.2 GPa, which is slightly lower than that of Example 4, but still at a relatively high level.
[0151] Wear rate: Wear rate is 1.35×10 -6 mm 3 / N·m, better wear resistance.
[0152] Friction coefficient: The friction coefficient is 0.09, and the self-lubricating coating performs well, but is slightly inferior to the solution of the present invention.
[0153] Bonding strength: The bonding strength is 63.2N, the highest among all the examples, indicating that the composite coating has a significant effect in improving the bonding strength.
[0154] Corrosion resistance: The corrosion potential is -0.20V and the corrosion rate is 0.012mm / year, showing the most excellent corrosion resistance and is very suitable for corrosive environments.
[0155] Summary of Examples
[0156] The solution of the present invention (Example 1) combines good hardness, wear resistance, low friction coefficient and excellent bonding force, is particularly suitable for heat-sensitive metal parts, and provides comprehensive performance improvement.
[0157] Embodiment 2: Suitable for high temperature working conditions, but inferior to the solution of the present invention in terms of hardness, bonding strength and corrosion resistance.
[0158] Embodiment 3: The gradient coating design improves stress distribution and bonding strength, which is suitable for complex stress environments.
[0159] Embodiment 4: It has the highest hardness and the lowest friction coefficient and is particularly suitable for the application of high-precision micro-mechanical parts.
[0160] Embodiment 5: It has the best corrosion resistance and is suitable for metal parts that are exposed to corrosive environments for a long time.
[0161] Each embodiment has unique advantages in different application scenarios, and the solution of the present invention demonstrates comprehensive performance advantages through multi-layer coating design and optimized process steps, and is suitable for surface enhancement treatment of various high-precision metal parts.
[0162] Comparative experimental design:
[0163] Purpose:
[0164] By designing a relatively complex comparative experiment, the performance of the prior art and the technical solution of the present invention in terms of coating hardness, wear resistance, friction coefficient, bonding force, corrosion resistance and other key parameters is compared. The experiment aims to verify the advantages of the technical solution of the present invention, especially the application effect in the surface enhancement of high-precision metal parts.
[0165] Existing technology:
[0166] Existing technical solution: Use traditional high-temperature chemical vapor deposition (CVD) technology to deposit multi-layer coatings, which are often used for wear-resistant and corrosion-resistant coatings on the surface of metal parts. The main process steps include:
[0167] Substrate pretreatment: The substrate is mechanically polished and ultrasonically cleaned.
[0168] Coating deposition: A single coating of titanium nitride (TiN) or chromium nitride (CrN) is deposited at a high temperature of 600-800°C using a CVD process with a total thickness of 5μm. The coating is bonded to the substrate by high-temperature diffusion.
[0169] Post-processing: Natural cooling, no special post-processing steps.
[0170] The technology of the present invention:
[0171] The technical solution of the present invention is to use a multilayer vacuum coating method combining low-temperature plasma enhanced physical vapor deposition (PE-PVD) and pulsed laser deposition (PLD). The main process steps include:
[0172] Substrate pretreatment: The substrate is processed by plasma cleaning and laser etching.
[0173] Coating deposition: PE-PVD technology is used to deposit titanium nitride / chromium nitride multilayer structure at 300°C, with each layer having a thickness of 50-100nm and a total thickness of 5μm. The surface layer is a composite self-lubricating coating of diamond-like carbon and molybdenum disulfide.
[0174] Post-treatment: coating densification is performed by ion beam assisted deposition (IBAD) and low temperature heat treatment.
[0175] Comparative Experimental Design Process
[0176] 1. Substrate selection
[0177] Substrate: Titanium alloy Ti6Al4V was selected as the experimental substrate, which is widely used in aerospace and high-precision mechanical parts manufacturing.
[0178] Size: The substrate sample size is 50mm×50mm×3mm to ensure the comparability of experimental data.
[0179] 2. Coating Preparation
[0180] Prior art coating preparation:
[0181] The chemical vapor deposition (CVD) process is used to deposit a single layer of titanium nitride or chromium nitride coating at a high temperature of 600-800°C, with a total thickness controlled at 5μm and no self-lubricating layer.
[0182] The substrate pretreatment steps are mechanical polishing and ultrasonic cleaning, and the coating is cooled naturally after deposition without ion beam assisted treatment.
[0183] Preparation of coating of the present invention:
[0184] The titanium nitride / chromium nitride multilayer coating was alternately deposited at 300°C using a plasma enhanced physical vapor deposition (PE-PVD) process with a total thickness of 5 μm.
[0185] The diamond-like carbon and molybdenum disulfide self-lubricating composite coating was deposited using pulsed laser deposition (PLD) technology, and the total thickness of the coating was 500nm.
[0186] Ion beam assisted treatment was added during the coating deposition process, and low-temperature heat treatment was performed at 200°C.
[0187] 3. Comparative experimental process
[0188] Coating thickness and morphology test:
[0189] The coating thickness was measured using an ellipsometer with an accuracy of 1 nm. The cross-sectional morphology of the coating was observed using a scanning electron microscope (SEM) to evaluate the coating uniformity and density.
[0190] Hardness test:
[0191] A nanoindentation tester was used to perform a hardness test to measure the hardness value of the coating. The coating hardness was calculated according to the Oliver-Pharr method. Each sample was subjected to 10 indentation tests and the average value was taken.
[0192] Wear resistance test:
[0193] The wear test was carried out using a ball-on-disc wear tester, with a steel ball (hardness 60HRC, diameter 6mm) selected as the counter-wear material. The test load was 10N, the sliding speed was 0.1m / s, the test distance was 1000m, and the wear rate was calculated.
[0194] Friction coefficient test:
[0195] The friction force was recorded using a ball-on-disc wear tester, the friction coefficient was calculated, and the self-lubricating properties of the coating were evaluated.
[0196] Bonding strength test:
[0197] The bonding strength between the coating and the substrate was tested using a scratch tester. The critical load was recorded by increasing the loading force until the coating peeled off.
[0198] Corrosion resistance test:
[0199] Electrochemical impedance spectroscopy (EIS) was used to test the corrosion resistance of the coating. The corrosion medium was 3.5% NaCl solution, and the corrosion potential and corrosion rate were measured.
[0200] 4. Experimental parameter settings
[0201]
[0202]
[0203] Comparative experimental data:
[0204]
[0205] Experimental data analysis:
[0206] 1. Hardness:
[0207] Existing technology: Due to the use of a single layer of titanium nitride or chromium nitride coating, the hardness is 17.5GPa. Due to the lack of a nano multilayer structure, the hardness of the coating is limited, and the deposition temperature is high, which may lead to stress concentration at the interface between the substrate and the coating.
[0208] The technical solution of the present invention: Through the titanium nitride / chromium nitride multilayer alternating structure, the hardness is significantly increased to 22.5GPa, and the Hall-Petch effect of the multilayer structure helps to enhance the hardness. The coating has high density and low deposition temperature, which reduces the thermal deformation of the substrate.
[0209] 2. Wear rate:
[0210] Existing technology: wear rate is 2.00×10 -6 mm 3 / N·m, the higher wear rate reflects the insufficient wear resistance of the coating, and the single-layer structure is prone to crack propagation during the wear process.
[0211] Technical solution of the present invention: The wear rate is 1.25×10 -6 mm 3 / N·m, the superiority of the nano-multilayer structure is obvious. The multilayer coating performs better in stress conduction and crack suppression. At the same time, the introduction of the self-lubricating layer further reduces wear.
[0212] 3. Friction coefficient:
[0213] Prior art: The friction coefficient is 0.15, showing a relatively high friction resistance. Especially in the absence of a self-lubricating layer, the friction performance of the coating is relatively poor.
[0214] The technical solution of the present invention has a friction coefficient of only 0.08, which is significantly better than the prior art, indicating that the composite self-lubricating layer of diamond-like carbon and molybdenum disulfide effectively reduces the friction coefficient and is particularly suitable for high-speed or dry friction environments.
[0215] 4. Binding force:
[0216] Existing technology: The bonding force is 40N. Although the CVD high-temperature coating has a certain diffusion bonding effect, the stress concentration between the coating and the substrate is large and the bonding force is low.
[0217] The technical solution of the present invention: The bonding force is 62.5N. The bonding force between the coating and the substrate is significantly enhanced by plasma enhanced PVD and ion beam assisted deposition. Low temperature deposition reduces thermal stress, and ion beam treatment improves the density and bonding strength of the coating.
[0218] 5. Corrosion resistance:
[0219] Existing technology: The corrosion potential is -0.40V, the corrosion rate is 0.035mm / year, and the single-layer coating is prone to cracks and pores in a corrosive environment, resulting in a decrease in corrosion performance.
[0220] The technical solution of the present invention: the corrosion potential is -0.25V, the corrosion rate is 0.016mm / year, the multi-layer structure and the composite coating significantly enhance the corrosion resistance, and the dense multi-layer coating on the surface effectively blocks the penetration of the corrosive medium.
[0221] Comparative experiment summary:
[0222] Hardness and wear resistance: The hardness and wear resistance of the technical solution of the present invention are significantly better than those of the prior art. The introduction of nano multilayer structure and self-lubricating coating shows obvious advantages in reducing wear and improving durability.
[0223] Friction coefficient: Through the diamond-like carbon and molybdenum disulfide self-lubricating coating, the solution of the present invention effectively reduces the friction coefficient, which is particularly suitable for scenarios where friction loss needs to be reduced, such as high-precision machinery and high-speed equipment.
[0224] Bonding strength: Ion beam assisted deposition technology significantly improves the bonding strength between the coating and the substrate, which is far superior to the traditional CVD process and is suitable for application scenarios with high bonding requirements.
[0225] Corrosion resistance: The scheme of the present invention also shows significant advantages in corrosion resistance. The composite coating design and low-temperature deposition effectively prevent the penetration of corrosive media, making the coating more durable in corrosive environments.
[0226] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts, characterized in that: The following steps are involved: S1. Surface treatment: plasma cleaning is used to remove pollutants and oxide layers on the substrate surface, and laser etching technology is used to roughen the substrate surface at a microscopic level; S2, coating deposition: depositing a metal transition layer on the substrate by plasma enhanced physical vapor deposition technology, and depositing a multi-layer nano hard coating on the transition layer; S3, self-lubricating layer deposition: self-lubricating coating is deposited on the multi-layer nano-hard coating by pulsed laser deposition technology; S4, post-treatment: the coating is post-treated using ion beam assisted deposition technology; S5. Heat treatment: Perform low-temperature heat treatment on the coating to eliminate the internal stress of the coating.
2. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the step S1, the plasma cleaning gas is argon, the gas flow rate is 200 sccm to 400 sccm, the plasma power is 300 W to 600 W, the cleaning time is 10 min to 30 min, and the processing pressure is controlled at 0.05 Pa to 0.2 Pa.
3. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the step S1, the laser etching technology uses a nanosecond laser with a wavelength of 1064nm and a laser energy density of 8J / cm 2 ~12J / cm 2 , the laser frequency is 10Hz~20Hz, the scanning speed is 2mm / s~5mm / s, and the surface roughness is controlled at 0.2μm~0.5μm.
4. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the step S2, the metal transition layer includes a titanium layer and a chromium layer, the thickness of the titanium layer is 100nm to 300nm, the thickness of the chromium layer is 100nm to 200nm, the metal transition layer is deposited by plasma enhanced physical vapor deposition technology, and the substrate temperature is controlled at 200°C to 300°C.
5. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the step S2, the multilayer nano hard coating includes alternately deposited titanium nitride and chromium nitride, the thickness of a single layer coating is 40nm to 120nm, the total coating thickness is 3μm to 10μm, and the number of layers is 50 to 150 layers.
6. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the S2 step, the coating hardness is calculated by the following formula: s y =σ0+k y ·d -0.5 Among them, σ y is the yield strength of the coating, σ0 is the yield strength of the defect-free grain material, k y is the material constant, d is the grain size, and the grain size is controlled between 30nm and 70nm to further improve the hardness and fatigue resistance of the coating.
7. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the step S3, the self-lubricating coating includes diamond-like carbon and molybdenum disulfide, the thickness of the self-lubricating coating is 300nm-700nm, and the self-lubricating coating is deposited at a substrate temperature of 200°C-300°C using pulsed laser deposition technology.
8. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the step S4, the ion beam energy of the ion beam assisted deposition technology is 800eV to 1500eV, and the ion beam current density is 8mA / cm 2 ~15mA / cm 2 The processing time is 20min to 40min.
9. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In the step S5, the low-temperature heat treatment step of the coating is carried out under the protection of an inert gas, the heat treatment temperature is 150° C. to 250° C., and the treatment time is 1 h to 3 h.
10. A multi-layer vacuum coating method for surface enhancement of high-precision metal parts according to claim 1, characterized in that: In step S5, the friction coefficient of the coating is calculated by the following formula: Where μ is the friction coefficient, F friction is the friction force, F normal is the normal force, and the friction coefficient between diamond-like carbon and MoS self-lubricating coating is controlled in the range of 0.05 to 0.1.
Citation Information
Cited By
Film coating control method and system based on data processing
CN120625024A
Method and system for improving NVH (Noise Vibration and Harshness) of driving shaft of pure electric vehicle based on new material application
CN120905495A
Atomic layer deposition process for surface hardening of lightweight steel
CN122235679A
A lightweight steel surface hardening atomic layer deposition process
CN122235679B